1997
DOI: 10.1002/(sici)1520-6793(199707)14:4<337::aid-mar3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of imagery-evoking radio advertising strategies on affective responses

Abstract: A debate in the marketing literature concerning the relative effectiveness of various imagery‐evoking strategies in influencing consumer responses to advertising has been unresolved. This study examined the effects of three imagery‐evoking strategies commonly used in radio advertising—sound effects, vivid verbal messages, and instructions to imagine—in influencing mental imagery, ad‐evoked feelings, and attitude toward the ad. The theoretical basis for the study is an imagery model based on propositional repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 14 publications
(32 reference statements)
2
42
0
Order By: Relevance
“…If people consciously allocate more cognitive resources to high-imagery ads than are required to encode the ad into memory, that means that more cognitive resources may be available for other cognitive tasks such as storing information from the ad in memory. Indeed, previous research has demonstrated that high-imagery advertisements are more memorable than low-imagery advertisements (Miller & Marks 1997;Unnava, Agarwal, & Haugtvedt 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If people consciously allocate more cognitive resources to high-imagery ads than are required to encode the ad into memory, that means that more cognitive resources may be available for other cognitive tasks such as storing information from the ad in memory. Indeed, previous research has demonstrated that high-imagery advertisements are more memorable than low-imagery advertisements (Miller & Marks 1997;Unnava, Agarwal, & Haugtvedt 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Imagery was conceptualized as a characteristic of advertisements that elicits imagery processing. Previous research has manipulated imagery through the presence or absence of production features known to elicit imagery processing (e.g., Miller & Marks, 1997). This type of manipulation of imagery is feasible for experiments where researchers produce their own stimulus messages.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale is that the vivid presentation hinders the individual's allocation of processing resources in making decisions, increasing positive affective responses (Shiv and Fedorikhin 1999). Miller and Marks (1997) compare the vividness of different imagery-evoking strategies in the radio ads, i.e., sound effects, vivid verbal message, and instructions to imagine. Their empirical results confirm the positive relationship between vividness and pleasant feelings.…”
Section: System Stimuli and Emotional Statesmentioning
confidence: 99%
“…Usually, information with animation, flash, audio, video or presented with colorful language is more vivid than that without additional sensory stimuli (Miller and Marks 1997;Steuer 1992). Empirical evidence shows that animated web advertising elicits stronger orienting responses (Lang et al 2002), faster click-through (Li and Bukovac 1999), and higher arousal (Heo and Sundar 2000) than the static ads.…”
Section: H 6c : the More Vivid The Online Stimuli The Stronger Is Thmentioning
confidence: 99%